1991
DOI: 10.1093/annonc/2.suppl_2.177
|View full text |Cite
|
Sign up to set email alerts
|

Prospective multicenter trial for the response-adapted treatment of high-grade malignant non-Hodgkin's lymphomas: Updated results of the COP-BLAM/IMVP-16 protocol with randomized adjuvant radiotherapy

Abstract: In a prospective multicenter trial the efficiency of the response-adapted COP-BLAM/IMVP-16 protocol to induce complete remissions (CR) in high-grade malignant non-Hodgkin's lymphomas as well as the prognostic relevance of adjuvant radiotherapy were investigated. From 1986-1989, 548 patients (median age 56 years) with stage II-IV (Ann Arbor) disease were treated with five cycles of COP-BLAM followed by two cycles of IMVP-16. If only a partial remission was obtained at the time of first restaging (RS) after thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

1992
1992
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(6 citation statements)
references
References 6 publications
0
5
0
1
Order By: Relevance
“…The explanation for a more favorable NPV obtained with the early scan would be that rapidity of achieving a complete response implies chemosensitivity of the tumor. Because high chemosensitivity usually translates into higher CR, this finding is probably a harbinger of sustained CR 23–25. In a seminal study of DLCL, Armitage et al reported when therapy was adjusted according to the response after 3 cycles in NHL, 73% of the patients achieved a CR 23.…”
Section: Discussionmentioning
confidence: 99%
“…The explanation for a more favorable NPV obtained with the early scan would be that rapidity of achieving a complete response implies chemosensitivity of the tumor. Because high chemosensitivity usually translates into higher CR, this finding is probably a harbinger of sustained CR 23–25. In a seminal study of DLCL, Armitage et al reported when therapy was adjusted according to the response after 3 cycles in NHL, 73% of the patients achieved a CR 23.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical data on VTE in HG-NHL were provided by the "Response-adapted COP-BLAM/IMVP-16 trial for Ann Arbor stage 11-IV HG-NHL with randomised adjuvant radiotherapy". The design of this prospective national multicentre study has been reported in detail elsewhere (12). In brief, 593 patients, aged 16-75 years, with previously untreated HG-NHL presenting with stage 11-IV disease (Ann Arbor classification) were treated with the COP-BLAM (13), but without dose escalation, and the IMVP-16 (14) regimens.…”
Section: Methodsmentioning
confidence: 99%
“…One trial was stopped early when the benefit of rituximab became evident, 12 or as a result of a planned interim analysis. 17 Older trials included lymphomas classified by the Kiel classification 18 or included DLBCLs according to the Working Formulation. 19 Six of the trials included patients with localized disease only, but five of the 11 trials included also advanced stages.…”
Section: Resultsmentioning
confidence: 99%